Cross-talk between cancer cells and their neighbors via miRNA in extracellular vesicles: an emerging player in cancer metastasis - Akiko Kogure; Nobuyoshi Kosaka; Takahiro Ochiya (Journal of Biomedical Science, 2019)
Abstract Cancer metastasis is the major cause of mortality in cancer cases and is responsible for cancer deaths. It is known that cancer cells communicate with surrounding microenvironmental cells, such as fibroblast cells, immune cells, and endothelial cells, to create a cancer microenvironment for their progression. Extracellular vesicles (EVs) are small vesicles that can be secreted by most types of cells and play an important role in cell-to-cell communications via transferring bioactive cargos, including variable RNAs, such as microRNAs (miRNAs), to recipient cells. miRNAs are a class of small noncoding RNAs that posttranscriptionally regulate gene expression. The transfer of them to recipient cells influences the metastatic process of primary tumors. In this review, we summarize the function of miRNAs packaged in EVs in cancer metastasis and discuss the clinical utility of miRNAs in EVs.